2021
DOI: 10.1093/braincomms/fcab008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of β-amyloid positivity in Alzheimer’s Disease Neuroimaging Initiative participants with demographics, cognition, MRI and plasma biomarkers

Abstract: In vivo gold standard for the ante-mortem assessment of brain β-amyloid pathology is currently β-amyloid PET or cerebrospinal fluid measures of β-amyloid42 or the β-amyloid42/β-amyloid40 ratio. The widespread acceptance of a biomarker classification scheme for the Alzheimer’s disease continuum has ignited interest in more affordable and accessible approaches to detect Alzheimer’s disease β-amyloid pathology, a process that often slows down the recruitment into, and adds to the cost of, clinical trials. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 98 publications
8
53
1
Order By: Relevance
“…An imbalance between production and clearance of Aβ occurs early in AD and is typically followed by the accumulation of tau (T in A/T/N) protein tangles (another key pathological hallmark of AD) and neurodegeneration (N in A/T/N) detectable on brain MRI scans ( Hardy and Selkoe, 2002 ; Sperling et al, 2011 ; Jack et al, 2016 ). Therefore, there has been great interest in developing techniques to associate Aβ and tau deposition with MRI measures ( Tosun et al, 2013 , 2014 , 2016 , 2021 ; Ten Kate et al, 2018 ; Petrone et al, 2019 ; Ansart et al, 2020 ; Ezzati et al, 2020 ; Sun et al, 2020 ; Dahl et al, 2021 ). In the structural MRI, the hippocampus is a primary target region across the spectrum of dementia research from clinically normal to late stages of AD ( Shi et al, 2011 ; Li B. et al, 2016 ; Dong et al, 2019 ; Cullen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance between production and clearance of Aβ occurs early in AD and is typically followed by the accumulation of tau (T in A/T/N) protein tangles (another key pathological hallmark of AD) and neurodegeneration (N in A/T/N) detectable on brain MRI scans ( Hardy and Selkoe, 2002 ; Sperling et al, 2011 ; Jack et al, 2016 ). Therefore, there has been great interest in developing techniques to associate Aβ and tau deposition with MRI measures ( Tosun et al, 2013 , 2014 , 2016 , 2021 ; Ten Kate et al, 2018 ; Petrone et al, 2019 ; Ansart et al, 2020 ; Ezzati et al, 2020 ; Sun et al, 2020 ; Dahl et al, 2021 ). In the structural MRI, the hippocampus is a primary target region across the spectrum of dementia research from clinically normal to late stages of AD ( Shi et al, 2011 ; Li B. et al, 2016 ; Dong et al, 2019 ; Cullen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the samples in these studies were clinical trial populations, the performance of these biomarkers in community-based populations was much worse. For example, one study in ADNI reported that among people who are cognitively impaired, plasma p-tau181 distinguished amyloid-positives with a moderate area under curve (AUC) of 0.67 (Tosun et al, 2021), much lower than the AUCs of 0.77-0.91 reported in some memory clinic cohorts (Karikari et al, 2020;Thijssen et al, 2020). Likewise, another study using a small cohort found that plasma p-tau181 discriminated 20 cognitively normal amyloid-positive people from 31 amyloidnegative people with an AUC of only 0.67 (Barthélemy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of different studies are still controversial. Studies adopting the SIMOA platform showed lower levels of plasma Aβ42 and Aβ42/Aβ40 in patients with AD than in controls (Janelidze et al, 2016 ; Li et al, 2019 ; Tosun et al, 2021 ). By contrast, some studies found that the levels of Aβ42 and Aβ42/Aβ40 were significantly increased in patients with mild cognitive impairment (MCI) or AD (Teunissen et al, 2018 ; Palmqvist et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%